PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN BAGUS HAYDEN HOTEL KUTA, BALI - Sanjiwani, I Made Amerthadi; Suana, I Wayan (E-Jurnal Manajemen, 2016)
Hotel is said to be the world who provide services service industry lodging accommodations. bermunculanya various models of the hospitality industry that provides services with a personal strength such as facilities, pose stiff competition. Bagus Hayden Hotel is one of the company service providers are already widely known accommodation in Kuta Bali. This study aimed to influence transformational leadership style, job satisfaction, and organizational commitment to employee performance at Bagus Hayden Hotel. With a data analysis technique multiple linear regression and using Slovin formula as much as 56 respondents. Analysis prove transformational leadership style, job satisfaction, and organizational commitment simultaneous and partial effect on the performance of employees at Bagus Hayden Hotel. job satisfaction dominant direct influence on the performance of employees at Bagus Hayden Hotel.
Keywords: kinerja; kepemimpinan transformasional; kepuasan kerja; komitmen organisasi